2015
DOI: 10.1093/mnras/stv954
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Bondi radius of M87

Abstract: Chandra X-ray observations of the nearby brightest cluster galaxy M87 resolve the hot gas structure across the Bondi accretion radius of the central supermassive black hole, a measurement possible in only a handful of systems but complicated by the bright nucleus and jet emission. By stacking only short frame-time observations to limit pileup, and after subtracting the nuclear PSF, we analysed the X-ray gas properties within the Bondi radius at 0.12 − 0.22 kpc (1.5 − 2.8 arcsec), depending on the black hole ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
162
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(191 citation statements)
references
References 127 publications
(200 reference statements)
29
162
0
Order By: Relevance
“…The inferred profile is steeper than the R R 3 2 ( ) r µ -profile expected for Bondi accretion in the circumnuclear regions of low accretion rate systems (Bondi 1952), and from the R R 1 ( ) r µ -profile inferred within the Bondi radius of Sgr A* and the AGN in M87 (Baganoff et al 2003;Russell et al 2015). The circumnuclear density profile inferred from radio observations of the relativistic TDE Sw J1644+57 is consistent with R R 3 2 ( ) r µ -but shows a hint of a steeper slope at R  0.05 pc, the smallest radius probed (Berger et al 2012).…”
Section: Synchrotron Emission Modelmentioning
confidence: 59%
“…The inferred profile is steeper than the R R 3 2 ( ) r µ -profile expected for Bondi accretion in the circumnuclear regions of low accretion rate systems (Bondi 1952), and from the R R 1 ( ) r µ -profile inferred within the Bondi radius of Sgr A* and the AGN in M87 (Baganoff et al 2003;Russell et al 2015). The circumnuclear density profile inferred from radio observations of the relativistic TDE Sw J1644+57 is consistent with R R 3 2 ( ) r µ -but shows a hint of a steeper slope at R  0.05 pc, the smallest radius probed (Berger et al 2012).…”
Section: Synchrotron Emission Modelmentioning
confidence: 59%
“…The cluster background accounts for up to 10% of the emission within the region covered by the nuclear point spread function. Reference [29] showed that the cluster surface brightness increases towards the nucleus in M87, therefore a background spectrum extracted in a surrounding annulus will likely underestimate the true background. Following [29], we have therefore used a ChaRT/marx PSF simulation to subtract the nuclear emission and evaluate the effect of the observed increase in the background cluster surface brightness.…”
Section: Data Reductionmentioning
confidence: 99%
“…Reference [29] showed that the cluster surface brightness increases towards the nucleus in M87, therefore a background spectrum extracted in a surrounding annulus will likely underestimate the true background. Following [29], we have therefore used a ChaRT/marx PSF simulation to subtract the nuclear emission and evaluate the effect of the observed increase in the background cluster surface brightness. The stellar population and unresolved low mass X-ray binaries contribute at most a few per cent of this background and are not considered further [36].…”
Section: Data Reductionmentioning
confidence: 99%
“…These conditions are easily met in astrophysics and atmospheric motion. The presence of a gradient of pressure, which is a sort of fluid group self force, renders the accretion motion non-geodesic.In accretion motion back reaction effects are taken into consideration in numerical and simulation analyses [1][2][3]. Full analytical treatments [4-8] drop back reaction effects for simplicity and cognitive treatments [9-15] may include emission effects and neglect back reaction too.…”
mentioning
confidence: 99%
“…In accretion motion back reaction effects are taken into consideration in numerical and simulation analyses [1][2][3]. Full analytical treatments [4][5][6][7][8] drop back reaction effects for simplicity and cognitive treatments [9][10][11][12][13][14][15] may include emission effects and neglect back reaction too.…”
mentioning
confidence: 99%